A Second Fungal Outbreak in Castañar Cave, Spain, Discloses the Fragility of Subsurface Ecosystems - Martin-Pozas, Tamara; Nováková, Alena; Jurado, Valme; Cuezva, Soledad; Fernandez-Cortes, Angel; Saiz-Jimenez, Cesareo; Sanchez-Moral, Sergio (Microbial ecology, 2024)
Castañar is a cave with strict visitor control measures since it was open to public visits in 2003. However, in recent years, the cave suffered two fungal outbreaks, the first in 2008 and controlled by cleaning the contaminated sediments and subsequent closure of the cave until 2014. The cave was reopened but limited to a maximum of 450 visitors/year. Despite these restrictions on visit, the cave experienced a second outbreak in 2021, originating from the installation of a steel grating walkway, aiming at protecting the ground sediments from the visitors' footsteps. Here, we conducted an analysis using Next-Generation Sequencing and culture-dependent techniques to investigate the fungal communities related to the second outbreak and compare with those present before the cave suffered the outbreak. The results show that the most abundant fungi involved in the 2021 outbreak were already detected in 2020, and even in 2008 and 2009, although the main species that originating both outbreaks were different, likely due to the different carbon sources introduced into the cave.
Keywords: Caves; Ecological changes; houby; Fungi; Ecosystem; Natural heritage; Cave works; epidemický výskyt choroby; jeskyně; ekosystém; Cephalotrichum microsporum; Disease Outbreaks; Španělsko; Spain; Neocosmospora solani; Anthropogenic disturbances